Fertilidade de Byrsonima pachyphylla A. Juss. em uma paisagem fragmentada do Cerrado - MELO, Marina da Silva (2010)
Physical aspects of the environment and intrinsic characteristics of the plant species determine its vital activities, such as reproduction. The goal of my work was to verify whether canopy coverage, plant size and density of B. pachyphylla influence their fertility. I calculated the density of B. pachyphylla within circles of 20 m radius around 30 individuals. I counted all flowers and fruits of every plant and measured their height and diameter at 30 cm from the base (DAB30). I quantified the canopy coverage taking photos of the canopy around the sampled plants and estimated the amount of light using the average of the covered area of photographs. I did linear regressions between fertility and density, canopy coverage and size of plant. I did not find any relationship between population density (r2 = 0.0090, p = 0.6188), neither canopy coverage (r2 = 0.0089, p = 0.6204), neither plant size (height: r2 = 0.0013, p = 0.8512 and DAB30: r2 = 0.0309, p = 0.3530) with the fertility of B. pachyphylla. These results demonstrate that fertility of B. pachyphylla is determined by other factors not investigated. The population density does not influence the attractiveness of pollinators, which seems to be more determined by the phenological behavior of plant. The light was an abundant resource for B. pachyphylla and do not limit the reproduction. The plant size is the result of the interaction of several factors and does not necessarily promote greater reproductive capacity.